Rasio Keuangan Selama Pandemi Covid-19 dan Nilai Perusahaan - Suwantara, I Nyoman Gede; Anggara, I Wayan Gde Wahyu Purna (E-Jurnal Akuntansi, 2024)
Share prices reflect changes in company value over time. It is likely that investments are generated by companies with strong financial performance, which can be a positive indicator of the company's growth and increase its market value. This research aims to determine the effect of financial ratios during the Covid-19 pandemic on company value. This research was conducted on all companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling method used a non-probability sampling method with purposive sampling technique and obtained 267 observations. The data collection method uses non-participant observation. The data analysis technique used is Statistical Product and Service Solution (SPSS) for Windows. The research results show that profitability, solvency, liquidity and activity have a positive and significant effect on company value. This means that profitability, solvency, liquidity and activity can increase company value and provide a positive signal to investors. Keywords: Firm Value; Profitability; Liquidity; Leverage; Activity